ZNACZENIE JĘZYKA W KREOWANIU WIZERUNKU MIASTA - Koszko, Marta (Scripta Neophilologica Posnaniensia, 2019)
Cities are the main centres of social, cultural life and economic development. They have always attracted newcomers not only because of new opportunities but also because of the feeling of belonging and uniqueness which people need. The attractiveness of a particular urban centre mainly rests on its image, which is created in relation to its own unique identity. The language of the city, which is present in the public space in the form of the linguistic landscape and which reflects the socio-cultural composition of the city, creates the identity. Both socio-cultural composition of a city (hence the languages spoken in the public space) and the linguistic landscape can create an image of a city which is either open for an interaction or presents limited interactional potential.